THE EFFECT OF BRAINSTORMING METHOD ON THE STUDENTS’ READING SKILL IN ELEVENTH GRADE - Elysa Rohayani; Mila Nirmala Sari Hasibuan (JURNAL EDUSCIENCE (JES), 2019)
This study aims to determine reading skill of students in Man Rantauprapat using a brainstorming method. The population in this study were all eleventh grade students of Man Rantauprapat. The sample were XI- IPA-2 And IPA-3 each of which 38 students. The method was used in this study is quasy experiment, data collection and multiple choice test. Data were analyzed using descriptive statistical analysis technique and t-test.Based on analyze data on experiment class for pre-test having average value is 75.92 and post test 34.47 increasing of 63.25% and standard deviation was 0.1365. in control class in pre-test is 35,13 and pot-test 68,68 and having increasing to be 50.88% with standard deviation is 0.1721. From the results of these classes of different test value at significant level α = 0.05 that is t-ccount = 3.475 and t-table = 1.668 by comparing between t-count > t-table or 3.475 > 1.668 it show that H0 is rejected and Ha is accepted and there is the effect of brianstorming method on the reading skill students’ in eleventh grade Student’s At Man RantauPrapat Academic Year 2019 is accepted and the result is show the highest score.